Effects of Replacing Dietary Monounsaturated Fat With Carbohydrate on HDL (High-Density Lipoprotein) Protein Metabolism and Proteome Composition in Humans. Issue 11 (November 2019) - Andraski, Allison B.; Singh, Sasha A.; Lee, Lang Ho; Higashi, Hideyuki; Smith, Nathaniel; Zhang, Bo; Aikawa, Masanori; Sacks, Frank M.
Abstract : Objective: Clinical evidence has linked low HDL (high-density lipoprotein) cholesterol levels with high cardiovascular disease risk; however, its significance as a therapeutic target remains unestablished. We hypothesize that HDLs functional heterogeneity is comprised of metabolically distinct proteins, each on distinct HDL sizes and that are affected by diet. Approach and Results: Twelve participants were placed on 2 healthful diets high in monounsaturated fat or carbohydrate. After 4 weeks on each diet, participants completed a metabolic tracer study. HDL was isolated by Apo (apolipoprotein) A1 immunopurification and separated into 5 sizes. Tracer enrichment and metabolic rates for 8 HDL proteins—ApoA1, ApoA2, ApoC3, ApoE, ApoJ, ApoL1, ApoM, and LCAT (lecithin-cholesterol acyltransferase)—were determined by parallel reaction monitoring and compartmental modeling, respectively. Each protein had a unique, size-specific distribution that was not altered by diet. However, carbohydrate, when replacing fat, increased the fractional catabolic rate of ApoA1 and ApoA2 on alpha3 HDL; ApoE on alpha3 and alpha1 HDL; and ApoM on alpha2 HDL. Additionally, carbohydrate increased the production of ApoC3 on alpha3 HDL and ApoJ and ApoL1 on the largest alpha0 HDL. LCAT was the only protein studied that diet did not affect. Finally, global proteomics showed that diet did not alter the distribution of the HDL proteome across HDL sizes. Conclusions: This study demonstrates that HDL in humans is composed of a complex system of proteins, each with its own unique size distribution, metabolism, and diet regulation. The carbohydrate-induced hypercatabolic state of HDL proteins may represent mechanisms by which carbohydrate alters the cardioprotective properties of HDL. Abstract : Supplemental Digital Content is available in the text.